2007
DOI: 10.1210/en.2006-1042
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Impaired Extrathyroidal Thyroxine to 3,5,3′-Triiodothyronine Conversion Maintain Normal Serum 3,5,3′-Triiodothyronine Concentrations

Abstract: For T(3) to mediate its biological effects, the prohormone T(4) must be activated by removal of an outer-ring iodine by the type 1 or 2 deiodinases (D1 and D2) with approximately 60% of the daily T(3) production in rodents being produced extrathyroidally through this pathway. To further define the role of these enzymes in thyroid hormone homeostasis, we backcrossed the targeted disruption of the Dio2 gene into C3H/HeJ (C3H) mice with genetically low D1 expression to create the C3H-D2KO mouse. Remarkably, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 20 publications
4
37
0
1
Order By: Relevance
“…The blood concentration of TSH is increased due to suppressed negative feedback from TH's. Analysis of the HPT axis in D2 knockout mice demonstrated a 2-3 fold increase in the circulating TSH concentration and 27-40 % increase in the T 4 level accompanied by reducing clearance of T 4 from plasma, but at normal levels of T 3 [22][23][24]. Hypothyroidism in diabetics induces the secondary dyslipidemia; it is characterized as elevated levels of TAG, TC, LDL and altered levels of HDL.…”
Section: Discussionmentioning
confidence: 99%
“…The blood concentration of TSH is increased due to suppressed negative feedback from TH's. Analysis of the HPT axis in D2 knockout mice demonstrated a 2-3 fold increase in the circulating TSH concentration and 27-40 % increase in the T 4 level accompanied by reducing clearance of T 4 from plasma, but at normal levels of T 3 [22][23][24]. Hypothyroidism in diabetics induces the secondary dyslipidemia; it is characterized as elevated levels of TAG, TC, LDL and altered levels of HDL.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that in response to a disruption in pituitary T4 signaling, multiple adjustments take place in the HPT, eventually preserving systemic euthyroidism. In fact, the pit-D2 KO mouse model represented yet another example that the HPT is wired to maintain normal serum T3 levels, in addition to most animal models of isolated or combined deiodinase deficiency (19).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with recent observations in C3H/HeJ D2 À/À compound mutant mice with D1 deficiency and deletion of D2, which were shown to maintain normal growth. (26) This notion is supported by a recent study suggesting that D2 may not play a physiologic role in growth plate chondrocytes. (27) The observed effects of the D2 Thr92Ala polymorphism on femoral neck BMD are in line with the importance of local availability of T 3 for bone formation.…”
Section: Discussionmentioning
confidence: 77%
“…Although earlier studies on the role and functional expression of iodothyronine deiodinase enzymes in the skeleton have been equivocal, (12,14,(22)(23)(24)(25) a recent study reported normal growth in mice with deficiencies in D1 and D2, indicating that D2 may not be critical in skeletal development. (26) This notion was supported in a recent study that demonstrated that D2 activity is restricted to mature osteoblasts, suggesting a possible role for D2 in mature osteoblast function. (27) Devising a study addressing the potential role of deiodinases, including D2, on skeletal metabolism is difficult in humans, but study of the effects of functional D2 polymorphisms on BMD and bone turnover in humans may shed light on this role.…”
Section: Introductionmentioning
confidence: 78%